2014
DOI: 10.1016/j.ajpath.2014.07.025
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoneutralization of Endogenous Aminoprocalcitonin Attenuates Sepsis-Induced Acute Lung Injury and Mortality in Rats

Abstract: Acute lung injury (ALI) secondary to sepsis is a complex syndrome associated with high morbidity and mortality. We report that aminoprocalcitonin (NPCT), an endogenous peptide derived from the prohormone procalcitonin, plays a critical role in the development of ALI during severe sepsis and is a suggested risk factor for sepsis morbidity and mortality. Lethal sepsis was induced in rats by cecal ligation and puncture (CLP). Two hours after CLP, an i.p. injection of 200 μg/kg of anti-rat NPCT antibody was follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 70 publications
(90 reference statements)
1
14
0
Order By: Relevance
“…It is therefore considered a gold standard tool for testing the success of CLP as a sepsis model, and for studying the efficacy of both SOBT and SOP extracts as novel antiseptic agents. In conjunction with the reports of Liu et al ( 13 ) and Tavares et al ( 27 ), data from the present investigation showed significantly increased PCT levels following CLP in rats. The increment of PCT in septic rats may be due to a continuous bulk-flow constitutive pathway, in which only limited conversion to mature calcitonin occurs ( 28 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is therefore considered a gold standard tool for testing the success of CLP as a sepsis model, and for studying the efficacy of both SOBT and SOP extracts as novel antiseptic agents. In conjunction with the reports of Liu et al ( 13 ) and Tavares et al ( 27 ), data from the present investigation showed significantly increased PCT levels following CLP in rats. The increment of PCT in septic rats may be due to a continuous bulk-flow constitutive pathway, in which only limited conversion to mature calcitonin occurs ( 28 ).…”
Section: Discussionsupporting
confidence: 92%
“…Sepsis is defined as infection with organ dysfunction and is a leading cause of mortality in Intensive Care Units worldwide . The ultimate cause of death is due to secondary development of life‐threatening organ dysfunction, which is thought to result, in part, from a dysregulated inflammatory response . The lung is one of the most vulnerable organs during sepsis .…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate cause of death is due to secondary development of life‐threatening organ dysfunction, which is thought to result, in part, from a dysregulated inflammatory response . The lung is one of the most vulnerable organs during sepsis . and acute lung injury develops early during the course of sepsis and is associated with high morbidity and increased mortality .…”
Section: Introductionmentioning
confidence: 99%
“…Elevated serum PCT was found to be associated with a higher mortality rate in a septic model [15], while immunoneutralization of PCT protected rats from lethal endotoxemia [6,16]. Thus, elevated serum PCT levels were associated with the progression of sepsis.…”
Section: : Pct and Renal Function In Hbv-aclfmentioning
confidence: 99%
“…Serum PCT rapidly increases in animal models after exposure to bacterial components and cytokines such as lipopolysaccharides (LPS), tumor necrosis factor-α (TNF-α), and IL-6 [18], and our previous study proved that hepatic macrophages are the cell source of hepatic PCT in acute liver failure [19]. The inhibition of PCT expression reduces the cytokine storm and rescues a mouse sepsis model [6,16]. Systemic inflammation and immune system dysregulation are thought to integrate with the main physiopathological pathway involved in the natural history of HBV-ACLF [14].…”
Section: Figurementioning
confidence: 99%